KEMAJUAN PENELITIAN DAN PUBLIKASI TENTANG KONSELING RELIGIUS: TINJAUAN DAN ANALISIS BIBLIOMETRIK - Harahap, Jumli Sabrial (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Counseling services during the time of the Prophet Muhammad SAW are reflected in the hadith, showing him as an extraordinary counselor. The purpose of this study is to see and analyze the development of scientific papers published in Scopus regarding religious counseling. The research method uses a literature review, especially using bibliometrics. Data retrieval was obtained from the Scopus website using the keyword